A Comparative Study of Sulamus Shibyan and Jurumiyah as Nahwu Book in Enhancing the Learning of Qawa'id - Fadlilah, Nurul; Kesuma, Guntur Cahaya; Wahidah, Yeni Lailatul; Khusen, Rahmad; Rasyid, Muhammad Zaini Zakir (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
This study analyzes the correlation between the Nahwu Sulamus Shibyan and Jurumiyah books in qowaid learning (al-Qawaid al-Nahwiyyah). The research aimed to compare both books based on Mackey's theoretical framework, which includes the aspects of selection, gradation, presentation, and repetition. Qualitative (library research) and comparative descriptive methods were used and the data were collected through documentation techniques and analyzed using content analysis. The findings revealed that Sulamus Shibyan applies an inductive approach while Jurumiyah applies a deductive method. Both books, designed for beginners, use simple language and rotary gradation with contextual presentation methods. However, they differ in repetition techniques. The study concluded that Sulamus Shibyan is more suitable and easier for beginners at Madrasah Tsanawiyah (MTs) Al Mubarok to understand al-Qowaid al-Nahwiyyah. This research contributed to determining the most effective textbook for novice Arabic learners, with Sulamus Shibyan recommended as a foundational guide for learning al-Qowaid al-Nahwiyyah in early-level Islamic education.